I²C interface controller for temperature data logger: article / Mohd Shahrul Azree Remly - Remly, Mohd Shahrul Azree (2012)
This project covers two important parts which are I²C (Inter-Integrated Circuit) and Temperature Data Logger system. This report summarizes the design of I2C interface controller for communication between the temperature sensor and processor in the data logger system. I²C (Inter-Integrated Circuit) is commonly used in serial protocols for data transfers and its interface controller is developed in HDL Verilog, and implemented on Xilinx’s Spartan FPGA Development Board. It will be integrated with temperature sensor to perform as a Temperature Data Logger.